(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the essence of psycholinguistics, its key categories, the object and subject of research, and the interrelation between psychological and linguistic components in the processes of text and speech. It also provides an in-depth analysis of the stages of speech activity and the cognitive-motivational and psychological phases of text perception and comprehension.